Mr Joyce Is Writing Foreign English - Senn, Fritz (FOCUS: Papers in English Literary and Cultural Studies, 2002)
“more languages to start with than were absolutely necessary” (U16.352) It takes little demonstration to know that Joyce’s prose contains a higher degree of words outside English than most other works offiction. One glance at Finnegans Wake is evidence enough; at least half a hundred foreign languages have been traced in it though most ofthem with only very sporadic appearances. This has even led to a widespread misconception that knowledge of many such foreign languages would essentially help understand the book. But Ulysses already is bristling with phrases and words in Latin, French, Italian German, Gaelic, Spanish, Hungarian, Greek, Hebrew, and many more.